Determination of some thermodynamical interaction parameters of polycaprolactone with some solvents by inverse gas chromatography - Saraç, A; Türe, A; Cankurtaran, Ö; Yilmaz, F (JOHN WILEY & SONS LTD, 2002)
The retention diagrams of polycaprolactone (PCL) were obtained between 70 and 140degreesC with solvents such as n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, isopropyl acetate, isobutyl acetate and tert-butyl acetate by an inverse gas chromatography technique. Some thermodynamical parameters, namely the weight fraction activity coefficient of the solvent at infinite dilution, Omega(1)(infinity), the Flory-Huggins interaction parameter, X-12(infinity), at infinite dilution of solvent, the hard-core interaction parameter, X-t(infinity), at infinite dilution of solute, and the effective exchange energy parameters, R12 in the equation-of-state theory, were determined for these polymer-solvent systems. In addition, the partial molar heat of sorption, Delta(H) over bar (1), (sorp), the partial molar heat of mixing, Delta(H) over bar (infinity)(1) of the solvents and the solubility parameter of the polymer, delta(2), were determined for these systems. n-Alkanes were particularly poor solvents but the esters studied were moderately good solvents for PCL. The solubility of the PCL did not change considerably with temperature in all the solvents studied. The values of interaction parameters were close to each other for PCL-ester systems studied. The solubility parameter of PCL, delta(2), was found to be around 10 (cal cm(-3))(1/2) at room temperature and decreases linearly with temperature. (C) 2002 Society of Chemical Industry.
Keywords: inverse gas chromatography; polycaprolactone; equation-of-state theory; polymer-solvent interaction; Polymer Science